Kripke’s Critique of Descriptivism Revisited - Pierre Baumann (Princípios, 2010)
This paper has two purposes: the first is to critically examine Kripke’s well-known arguments against Descriptivism and suggest that they are not as decisive as many have thought; the second is to argue that proper names do encode descriptive information of various kinds, that such information may be truth-conditionally significant, and hence that a name’s truth-conditional contribution is not limited to its referent.